Charged sequence motifs increase the propensity towards liquid–liquid phase separation - Szabó András László; Sánta Anna; Pancsa Rita; Gáspári Zoltán (FEBS LETTERS, 2022)
Protein phase separation is a major governing factor in multiple cellular processes, such as RNA metabolism and those involving RNA-binding proteins. Despite many key observations, the exact structural characteristics of proteins involved in the phase separation process are still not fully deciphered. In this work, we show that proteins harbouring sequence regions with specific charged residue patterns are significantly associated with liquid–liquid phase separation. In particular, regions with repetitive arrays of alternating charges show the strongest association, whereas segments with generally high charge density and single α-helices also show detectable but weaker connections. © 2022 The Authors. FEBS Letters published by John Wiley & Sons Ltd on behalf of Federation of European Biochemical Societies.